Creating an effective learning environment through an e-learning instructional programme (ELIP) - Jakovljevic, Maria (Array, 2009)
Summary: Though numerous research reports have provided a body of information about benefits of e-learning there are barriers such as, asynchronous communication channels, lack of personalisation, which decrease the level of interaction between the learner and instructor [13]. The aim of this paper is to discuss and outline a framework on e-learning pedagogical and technology issues which provide a basis for the creation of an e-learning instructional programme (ELIP). The Phase I of this research start with the creation of a framework for an e-learning environment and derivation of the e-learning instructional programme (ELIP); Phase II is aimed to implement a popular audio playback device (iPod) and VoIP.